Demographic and Clinical Evaluation of Patients with Meningitis in a Hospital of Bangladesh - Chowdhury, Nazmul Hassan; Hasan, Abdullah Al; Azad, Abul Kalam; Das, Panchanan; Emran, Masum; Akther, Maher (Journal of Comilla Medical College Teachers’ Association, 2023)
Background: Meningitis is an inflammatory disease of the leptomeninges, the tissues surrounding the brain and spinal cord. It is a life threatening central nervous system infection that is prevalent worldwide. The lack of rapid and sensitive tests remains a key issue in diagnosing meningitis and affordability impedes accessing molecular techniques in diagnosing. The challenge of this disease is the emergency identification and prompt treatment required to enable survival, reduce mortality and prevent long-term sequelae. Objectives: The aim of this study was to evaluate the demographic and clinical profile of meningitis in a tertiary care hospital in Bangladesh. Methods: This was a cross-sectional observational study conducted in the Department of Neurology at Comilla Medical College Hospital, Cumilla, Bangladesh, during the period from July 2018 to June 2019. A total of 159 patients were enrolled in this study. All cases were diagnosed based on clinical or laboratory criteria. Detailed demographic data were collected and recorded in a structured case report form. Results: Among the159 patient, 69 were male and 90 were female. The mean ages are 31±20.03 years. The highest number of patients were presented with fever (100%), headache (90%), vomiting (47%) and altered mental status (37%). Among all 159 case of meningitis 62(39%) were bacterial meningitis, 55 (35%) were viral meningitis and 42 (26%) were tubercular meningitis. Diagnosis was made on the besis of clinical findings and radiological, biochemical and CSF study. Regarding seasonal variations, there are 2 peaks: summer and winter, which are responsible for viral and bacterial meningitis, respectively. Conclusion: Meningitis is a deadly infection that can spread rapidly if not taken early management. So, proper and rapid detection and other investigational facilities reduce the disability. J Com Med Col Teachers Asso Jan 2023; 27(1): 19-26